Factors Related to Body Mass Index in Women with Rheumatoid Arthritis – TOMORROW study - Matsumoto, Yoshinari; Sugioka, Yuko; Tada, Masahiro; Okano, Tadashi; Mamoto, Kenji; Inui, Kentaro; Habu, Daiki; Koike, Tatsuya (Journal of Nutritional Therapeutics, 2014)
Objectives: This study aimed to clarify the relationship between body mass index (BMI) and patient characteristics, lifestyle factors, and cardiovascular disease (CVD)-related clinical data in women with rheumatoid arthritis (RA). Methods: A total of 171 female outpatients with RA and 170 age-matched females without RA (controls) from the TOMORROW study (UMIN: 000003876) were included in this cross-sectional study. We divided subjects into 3 groups based on BMI: underweight (BMI < 18.5 kg/m2), normal weight (BMI ≥ 18.5 kg/m2 and < 25 kg/m2), and overweight (BMI ≥25 kg/m2), and compared RA disease activity, activities of daily living (ADL) assessed by modified health assessment questionnaire (mHAQ) score, energy and nutrient intake, and CVD risk-related clinical data. Results: In patients with RA, mHAQ scores were lower in the normal weight group compared with the underweight and overweight groups (p < 0.05). Disease activity showed a similar trend. Energy, protein, and carbohydrate intake showed a positive correlation with BMI (p < 0.05). Blood pressure, C-reactive protein, uric acid, triglyceride, fasting plasma glucose, immune reactive insulin, HbA1c, and leptin showed a positive correlation with BMI, and adiponectin showed a negative correlation with BMI (p < 0.05). Control subjects showed similar trends. Conclusions: BMI is related to ADL, disease activity, energy, protein and carbohydrate intake, and CVD risk-related clinical data, and might be an indicator of total health status in female patients with RA.